Pengaruh Efikasi Diri Akademik terhadap Hasil Belajar Geografi Fase F SMA Negeri 1 Linggo Sari Baganti Kabupaten Pesisir Selatan - Oktavia, Widia; Rahmanelli, Rahmanelli (Lembaga Yasin AlSys, 2024)
The purpose of this study was to analyze whether there is a positive and significant influence of academic self-efficacy on the learning outcomes of geography phase F of SMA Negeri 1 Linggo Sari Baganti, Pesisir Selatan Regency. The type of research used is quantitative research with a correlational approach. The location of the study was at SMA Negeri 1 Linggo Sari Baganti, Pesisir Selatan Regency. The research period was April 22 to May 22. The population in this study were students of phase F who taught geography subjects at SMA Negeri 1 Linggo Sari Baganti, Pesisir Selatan Regency. The number of samples was 97 people using the total sampling technique. Data collection techniques used in this study were observation, surveys, and documentation records. The data analysis procedure technique in this study used validity tests, reliability tests, descriptive statistical analysis, normality tests, linearity tests and hypothesis tests. The results of this study concluded that 1) There is a significant relationship between academic self-efficacy and student learning outcomses at phase F of SMA Negeri 1 Linggo Sari Baganti, Pesisir Selatan Regency as indicated by a significant correlation level value of 0.000 which is smaller than 0.05. This means that the academic self-efficacy variable has an effect on the learning outcome variable. 2) The academic self-efficacy of students in phase F of SMA Negeri 1 Linggo Sari Baganti Pesisir Selatan as a whole is in the low classification, which can be seen from the pie chart and the academic self- efficacy percentage table. 3) The learning outcomes of students in phase F of SMA Negeri 1 Linggo Sari Baganti as a whole are in the context of the less group, based on the calculation of the pie chart and the Learning Outcome Criteria (KKTP) table set by the school.